Movements of dingoes on K'gari-Fraser Island: implications for management. Issue 1 (2nd January 2018) - Baxter, Greg; Davies, Nicole
ABSTRACT: Dingoes ( Canis lupus dingo ) on K'gari-Fraser Island have interacted with humans in unacceptable ways, with regular attacks and even a death of a child. Public interest in maintaining a viable dingo population on the island is intense. Hence, there is an imperative to improve the management of dingo–human interactions, and knowledge of dingo movement behaviour can assist in this effort. Eighteen dingoes (10 female, 8 male) were captured in 2011 and fitted with GPS collars programmed to record a location every two hours. Dingoes were monitored for an average of slightly more than 205 days. Total home range sizes ranged from 547 to 57, 459 ha. (95 per cent fixed kernel estimate). Home ranges were also calculated for each animal during different phases of the breeding cycle. We identified four general types of movement: beach dwellers, predominantly coast and beach dwellers, coast to coast movers and mostly inland dwellers. There are some animals that have minimal chance of ever interacting with humans. There was a seasonal change in home range size with dingoes of both sexes moving further when they did not have dependent young. The home ranges we measured were comparable with mainland dingoes, offering no evidence that prey is scarcer than on the mainland.